Riccardo Moratto, Nicoletta Pesaro, and Di-kai Chao. (Eds.). (2022). Ecocriticism and Chinese Literature: Imagined Landscapes and Real Lived Spaces. - Enescu, Ioana Clara (Journal of Ecohumanism, 2023)
Riccardo Moratto, Nicoletta Pesaro, and Di-kai Chao. (Eds.). (2022). Ecocriticism and Chinese Literature: Imagined Landscapes and Real Lived Spaces. Routledge. DOI: 10.4324/9781003212317. ISBN: 978-1-003-21231-7 (ebk)